Teaching the Culture of Speech Communication in the Iranian Class - Azin Maryam Rezaei; Peyman Golestan (Высшее образование в России)
he article addresses the issue of teaching the culture of speech communication and behavior in the process of teaching Russian as a foreign language to Iranian students-philologists. The authors substantiate the necessity of singling out the category of speech etiquette and speech behavior in the process of teaching the Russian language and the importance of knowledge about the norms of communication accepted in the Russian linguacultural community and in intercultural communication. The article states that teaching the Russian language in the Iranian classes with an emphasis on the stylistically correct formulation of speech and taking into account the socio-cultural factor will contribute to the achievement of a high level of professionalism and will allow to prepare philologists in the field of intercultural communication. The authors suggest methodological recommendations on teaching the culture of Russian speech communication in the Iranian classes based on their experience of teaching Russian as a foreign language.